Potret Hukum Pertambangan di Indonesia dalam Era UU No. 4 Tahun 2009 - Soedarso, Bambang Prabowo (UI Scholars Hub, 2009)
According to Blackslaw dictionary, the definition of Mining law is the act of appropriating a mining claim (parcel of land containing precious metal in its soil or rock) according to certain established rule. Basically, State is entitled full authority to explore and exploit their natural resources. In practice, State is represented by company to explore and exploit its natural resources. Therefore, State creates mining law to provide basic principles and to regulate activities on mining industry. This article provides a full picture of the Indonesian mining law industry from many aspects, start from the colonial period until the present tie.